Dentoskeletal Class II Malocclusion: Maxillary Molar Distalization with No-Compliance Fixed Orthodontic Equipment - Vincenzo Quinzi; Enrico Marchetti; Luigi Guerriero; Floriana Bosco; Giuseppe Marzo; Stefano Mummolo (MDPI AG, 2020)
Dentoskeletal class II malocclusion due to a protruded upper dental arch is a major reason for an orthodontic treatment. In these cases, the correction of class II can be hindered by molar distalization, obtained with ‘no-compliance therapy’ that involves the use of appliances which minimize the need for such co-operation and attempt to maximize the predictability of results. The aim of this review was to outline the effectiveness of no-compliance fixed orthodontic devices in the molar distalization. After selection according to the inclusion/exclusion criteria, 16 articles from 2000 to 2019 were qualified for the final analysis. The literature shows various no-compliance fixed devices whose effect is to distalize the maxillary molars. The present revision allows to conclude that there is a need to increase the number of studies, especially with regard to the most recently introduced devices in the literature. The analysed studies allow to hypothesize that these appliances act with a minimal variability of molar distalization and disto-inclination among them, although different effects among the appliances can be observed as regards to the anchorage.